2016
DOI: 10.1073/pnas.1604693113
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis cluster 1 proteins form cytoplasmic arrays in Vibrio cholerae and are stabilized by a double signaling domain receptor DosM

Abstract: Nearly all motile bacterial cells use a highly sensitive and adaptable sensory system to detect changes in nutrient concentrations in the environment and guide their movements toward attractants and away from repellents. The best-studied bacterial chemoreceptor arrays are membrane-bound. Many motile bacteria contain one or more additional, sometimes purely cytoplasmic, chemoreceptor systems. Vibrio cholerae contains three chemotaxis clusters (I, II, and III). Here, using electron cryotomography, we explore V. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 54 publications
0
60
0
Order By: Relevance
“…V. cholerae encodes three distinct chemotaxis systems (cluster I, II, III) and 44-45 different MCPs [48]. The MCPs that are known to interact with cluster II all belong to the 40H class [22,49]. Cluster II arrays sense a plethora of cues and are so far the only chemosensory system that controls the chemotactic swimming behavior of V. cholerae [50].…”
Section: Discussionmentioning
confidence: 99%
“…V. cholerae encodes three distinct chemotaxis systems (cluster I, II, III) and 44-45 different MCPs [48]. The MCPs that are known to interact with cluster II all belong to the 40H class [22,49]. Cluster II arrays sense a plethora of cues and are so far the only chemosensory system that controls the chemotactic swimming behavior of V. cholerae [50].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of V. parahaemolyticus swimmer cells for fluorescence microscopy was carried out essentially as described (Ringgaard et al, 2015; Briegel et al, 2016). A volume of 10 mL of LB was inoculated with a bacterial colony of V. parahaemolyticus from an over-night LB agar plate grown at 37°C and relevant antibiotic.…”
Section: Methodsmentioning
confidence: 99%
“…The genome of V. cholerae encodes three chemosensory systems: F6, F7 and F9 (Table S2) (9). Having already identified the F6 and F9 systems (11,16), we hypothesized that the novel arrays were formed by the F7 system. The genome of P. aeruginosa encodes four chemosensory systems: F6, F7, ACF and TFP (Table S2) (9).…”
Section: F7 Array Architectures Correspond To the Domains Of Their Aementioning
confidence: 99%
“…showed that this array is formed by proteins of the F6 chemosensory system (16) (known to control flagellar rotation). In late stationary phase, we found that cells contain another, purely cytoplasmic array consisting of two CheA/CheW baseplates 35 nm apart sandwiching a double layer of chemoreceptors (16). This array is formed by proteins of the F9 chemosensory system, but its function is unknown.…”
mentioning
confidence: 99%